Customer Ethnocentrism, Animosity and Purchase Intentions of Chinese Products - Rai, Puneet (Journal of Contemporary Research in Management (JCRM), 2019)
The paper explores the relationship between customer ethnocentrism, animosity and purchase intentions of Chinese products in the Indian market. The study fulfills a gap in the extant literature as there is a dearth of studies exploring these relationships in India, a developing country for product from another country China that is at the intermediate level of development. The results of the study indicate that there are no differences in customer ethnocentric tendencies and animosity towards China across gender, income class who have similar education background. The study found that animosity towards China amongst customers has a strong influence on the purchase intention of Chinese product, while customer ethnocentric tendencies do not influence the purchase intention of Chinese product.